English Live Caption in a Javanese Shadow Puppet Theatre: Systemic Functional Linguistics for Appraising the Beauty of Sagopi - Dyah Ayu Nila Khrisna; Djatmika Djatmika (Institut Agama Islam Negeri (IAIN) Kendari, 2022)
In the field of simultaneous translation, live captioning has not been sufficiently touched by research. There have been shifts in translating characterization due to this being done in real-time and on the spot. It is critical that target readers or viewers get the same impression of a character's personality as portrayed in the original work. Consequently, translations of literary plays must be thoroughly checked for fidelity. The objective of the study is to undertake an in-depth analysis of the live captioning provided in